INTEGRATING AND LEVERAGING METADATA IN A SHARED ENVIRONMENT: THE UNIVERSITY OF MACAU EXPERIENCE [ARTICLE] - Pun, Priscilla (Nazarbayev University Library, 2021)
Library cataloging and metadata have been evolving since the mid-1990s, at the emergence and development of the World Wide Web and communication technologies. The purpose of the paper is to have a brief review of the development history of the cataloging and metadata practices of the University of Macau (UM) Library, in order to demonstrate the transitive changes from traditional cataloging to the promotion and preparation for structured data management, including the shift from static and single-source catalog to dynamic and multi-sources discovery platform. The value of the library’s bibliographic data is in sharing and reusing data locally, regionally and globally. Library cooperation and continuing education of the library staff are essential to this goal. A recent project entitled MALA Hub is introduced in the paper as well. It is a region-wide academic resource sharing project that initiated and launched its first phase in 2019, with the sponsorship of Macau SAR Government. The purpose of the project is to pool together, disclose, and share with each other all kinds of resources available for the nine library members of Macau Academic Library Alliance (MALA) in Macau, including physical pieces, consortium subscribed resources, individual library paid resources, open access resources, and in-house developed digital resources from the libraries and the community. In addition, derived from the MALA Hub by leveraging metadata integrated on the Hub, are several topic-specific resource portals suggested by the government and the community. The first topic-specific portal, Portuguese Portal (covering all available resources in Portuguese language), was launched at the end of 2019. More portals are planned to be launched in the near future, such as the Macau Study Portal, and the Specialized Collections Portal, among others.
Keywords: Type of access: Open Access; EALC; library